Hydrodynamic features and fractal dimension study for aerobic granulation in sequencing batch reactor [electronic resource] - Tijani Hamzat Ibiyeye, 1991-; Norhayati Abdullah, supervisor (2014)
Thesis (Sarjana) - Universiti Teknologi Malaysia, 2014